Two new species of Rhopalopsole vietnamica group (Plecoptera: Leuctridae: Rhopalopsole) from China - Li, Weihai; Yang, Ding (Zootaxa, 2010)
The following two species from Hainan and Ningxia, China are described as new to science: Rhopalopsole hainana sp. n. and R. ningxiana sp. n., respectively. Their relationship to similar species is discussed.